PENGUATAN KETAHANAN PANGAN KELUARGA MELALUI BUDIDAYA HORTIKULTURA PEKARANGAN DI DUSUN MONGGE 2 - Dewi, Suprayanti Martia; Nikmatullah, Aluh; Sarjan, Muhammad; Haryanto, Hery; Jihadi, Amrul (Universitas Mataram, 2025)
This community service activity aims to provide assistance in the development of horticultural cultivation in Dusun Mongge 2, Sukadana Village. The activity is a follow-up to the horticulture training conducted in early October 2023 at the Sukadana village office. The assistance is carried out in the form of hands-on gardening practices by local residents, particularly housewives, with the hope of improving household food security and creating home-based business opportunities. Support was provided in the form of horticultural seeds (eggplant, tomato, chili, bitter melon, zucchini, golden mama, etc.), polybags, soil, rice husks, manure, and plant protection nets. The assistance process is conducted periodically and includes technical education on cultivation, management of growing media, and the use of organic waste (livestock manure) as fertilizer. This approach aims to reduce dependence on chemical fertilizers while improving soil fertility and crop quality. Preliminary results show good plant growth and enthusiastic participation from the residents. It is hoped that this activity will not only strengthen household food security but also serve as an alternative source of income, particularly for housewives without permanent employment.